As apropriações das ideias educacionais de John Dewey na antiga Escola Normal Secundária de São Carlos SP - Varotto, Michele (Universidade Federal de São Carlos, 2012)
The aim of this research is to analyze how the ideas of John Dewey influenced and became theoretical-methodological guides for teacher s education in a Teacher`s College in São Paulo State, Brazil. In order to do that the methodology used was based in Dermeval Saviani s categories. Indeed to understand how Dewey s educational ideas were presented in Brazil is a very important investigation to be carried out. As result in this research through the reading and analyzes of a journal published between 1916- 1923 an effort was made to capture and comprehend the presence of Dewey`s ideas. The results point out that John Dewey`s educational thoughts were present in this teachers college and psychology teachers were responsible for teaching it. Dewey`s ideas were appropriate by this teachers before its formal entrance in Brazil in 1932. This is an important data for researches who works to understand how and when Dewey`s ideas were incorporated to our pedagogical knowledge.
Keywords: Educação; Dewey, John, 1859-1952; Escola normal; Escola nova; John Dewey, Normal School; New School.; CIENCIAS HUMANAS::EDUCACAO